PATTERN OF CLINICAL PRESENTATION AMONG INFERTILE HYPERPROLACTINEMIC FEMALES - , MEHWISH; HIRA, AK; NAZ, U; NAZ, U; SHEIKH, AH; MAZHAR, R (Biological and Clinical Sciences Research Journal, 2022)
The current prospective study was designed to assess the pattern of clinical presentation among infertile hyperprolactinemic females. This study was conducted at the Gynaecology Department Civil Hospital Karachi from March 2020 to Dec 2020. A total of 110 infertile women who visited the Gynaecology department of the hospital were included in the study. A sample of the subjects with regular menstrual cycles was collected on the second or third day after fasting for 8-12 hours overnight. Samples of the patients with irregular menstrual cycles or amenorrhea were collected randomly after overnight fasting. ELISA technique was used for quantifying serum prolactin. A total of 110 infertile women were evaluated, of which 58 (52.7%) were hyperprolactinemic. The clinical presentation included galactorrhea (27.5%) followed by a mixed presentation (22.4%), menstrual abnormalities(15.5%), recurrent abortion(8.6%), and hirsutism (3.4%).22.4% of patients were symptomless. The most common pattern of presentation of hyperprolactinemic infertility was galactorrhea; a larger sample was symptomless.